FORMULATION AND EVALUATION OF NOVEL ANTIBACTERIAL AND ANTI-INFLAMMATORY CREAM CONTAINING MUNTINGIA CALABURA LEAVES EXTRACT - Sekar, Mahendran; Abdul Jalil, Nur Syahira (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â Â Objective: The main objective of the present study was to formulate antibacterial and anti-inflammatory cream using Muntingia calabura leaves extract. Methods: 500 g of matured leaves of M. calabura were extracted with 70% methanol using maceration method for a week. The antibacterial activity of the extract and formulated cream in different concentration was investigated against two Gram-positive bacteria (Staphylococcus aureus and Bacillus cereus) and two Gram-negative bacteria (Escherichia coli and Pseudomonas aeruginosa) through disc diffusion method. The anti-inflammatory activity of extract and formulated cream was studied using inhibition of albumin denaturation technique. Results: The antibacterial activity of the methanolic extract was studied in different concentrations (5, 10, and 25 mg/ml) and the formulated cream was studied in the concentration of (10, 25, 50, and 100 mg/ml). The extract showed significant antibacterial activity with all the tested pathogens with a zone of inhibition ranges from 3.33 Â± 0.88-14.60 Â± 0.80 mm. As for the formulated cream, the zone of inhibition for F1 ranged from 0.67 Â± 0.67 mm to 14.80 Â± 1.17 mm. F2 presented zone of inhibition at 3.40 Â± 1.64 mm to 15.00 Â± 1.18 mm. The anti-inflammatory activity showed maximum inhibition of 63.93 Â± 5.90, 41.83 Â± 5.64, and 27.20 Â± 2.72 was observed at 1000 Î¼g/ml for the extract, F2 and F1, respectively. The cream was found to be in stable state after 2 months. Conclusion: The results showed that the formulated cream can be used for bacterial infections and to reduce inflammation. We recommend this formulation need to be further developed into commercial standards.